Tradisi Bondang: Kearifan Lokal dalam Menanam Padi di Desa Silo Lama, Kabupaten Asahan - Juniani, Ella; Dora, Nuriza (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The bondang tradition is a unique practice that has involved the people of Silo Lama Village for centuries in planting rice. This research examines the Bondang Tradition as a manifestation of local wisdom in the practice of planting rice in Silo Lama Village, Asahan Regency. The aim of this research is to document and analyze the bondang tradition and its impact on rice farming and the culture of the people in the village. This research is qualitative research, more precisely a research strategy that tries to describe the item or subject being studied. Therefore, in this review, to obtain information, researchers used subjective techniques. The research results show that the bondang tradition has deep roots in the history of agriculture in Silo Lama Village, and has become an integral part of the community's daily life. This practice not only affects rice yields, but also has significant cultural value, binding communities and strengthening local identity. This research also discusses the challenges faced by the bondang tradition in facing social and environmental changes. This research highlights the importance of preserving local traditions in agricultural and cultural contexts.